PENGARUH EKSTRAK ETANOL DAUN MAHKOTA DEWA (Phaleria macrocarpa (Scheff Boerl) TERHADAP AKTIVITAS SEL NK DAN MAKROFAG MENCIT - , Muhammad Gufron, Drs.,MS. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: A study has been conducted on leaves of mahkota dewa (Phaleria macrocarpa Scheff Boerl), a species of native Indonesian herb that based on empirical evidence is known to show medicinal properties. Obyective: To investigate the effect of mahkota dewa leaves etanol extract on activity of macrophages and natural killer (NK1.1) cells. experiments have been conducted in vitro. Macrophage activity includes phagocytosis, ROI secretion and IL-12 synthesis. Natural killer (NK1.1) cell activity comprises cytotoxicity, NKG2D, CD122 receptors expression and IFNÎ³ synthesis. Methods: Balb/C strain mice were used to test macrophage activity while C57BL/6 strain mice were used to test NK1.1 activity. There were eight treatment groups consisting of five mice in each. Group I, II and III, were treated using 1,05, 2,10 and 4,20 mg/20 g of body weight of mahkota dewa leaves etanol extract. respectively, following the 30 days of treatment the mice were sacrificed. Group IV, V and VI were treated at the dose similar to that given to the first 3 groups. These group were then inoculated with 10 4 cfu. of L. monocytogenes. Following the 48 hours incubation the sample was then sacrifice. Group VII as untreated control group was given carboxyl methyl cellulosa Na 0,5%, then group VIII was inoculated with 10 4 cfu L. monocytogenes. Result: Mahkota dewa leaf etanol extract is able to enhance macrophage phagocytosis and ROI secretion. At the dose of 4,20 mg/20 g of body weight gives powerful effect on phagocytic activity by 308% and ROI secretion activity by 214%. Meanwhile, at dose of 2,10 mg/20g of body weight phagocytic activity increase 348% and ROI secretion 395% on the additionally L. monocytogenes infected mice. This extract do not affect macrophage IL-12 synthesis however, it can induce the IL-12 synthesis when mice are additionally infected by L. monocytogenes. The most effective effect is at the dose of 2,10 mg/20 g of mouse body weight with the IL-12 expression of 47%. The dose of 4,20mg/20g of body weight gives the most powerful effect on cytotoxic activity of NK1.1 cells, 59% of target cells YAC-1 undergos to apoptosis. Whereas, at the dose of 2,10, mg/20g of body weight shows the strongest cytotoxic activity against YAC-1 (78%) on the NK1.1 cell of the additionally L. monocytogenes infected mice. The most effective dose on intensifying the expression of CD122 receptor (75%) is 4,20mg/20g of body weight. Whereas, the most effective dose on additionally L. monocytogenes infected group is 2,10 mg/20g of body weight with the expression of CD122 receptor of 79%. Similarly, this extract has the ability to enhance the expression of NKG2D receptor about 86%. In the event of additionally L .monocytogenes infection, 2,10 mg/20 g is the most effective dose on improving the expression of NKG2D receptors at 94%. At the dose of. 4,20 mg/20 g of body weight, the extract has the strongest effect on IFNÎ³ synthesis, about 44% NK1.1 express IFNÎ³ cytoplasmic on the uninoculated mice and 76% on the additionally innoculated L. monocytogenes mice. Conclusion: Mahkota dewa leaf etanol extract is able to enhance macrophage activity on phagocytosis and ROI secretion. This extract affect on cytotoxic activity, expression of CD122, NKG2D receptors and on synthesing IFNÎ³ of NK1.1 cells.